Integrated nutrient management improves soil organic matter and agronomic sustainability of semiarid rainfed Inceptisols of the Indo‐Gangetic Plains. Issue 5 (1st August 2021) - Srinivasarao, Ch.; Singh, S. P.; Kundu, Sumanta; Abrol, Vikas; Lal, Rattan; Abhilash, P. C.; Chary, G. R.; Thakur, Pravin B.; Prasad, J. V. N. S.; Venkateswarlu, B.
ABSTRACT: Background: Climate and management practices impact the soil organic carbon (SOC) stocks of agricultural soils. Especially under the semiarid climate of India, organic matter is rapidly decomposed, and imbalanced nutrient input further exacerbates its depletion, thus facilitating the decline in soil quality and crop yields. Improving SOC contents through integrated nutrient management (INM), that is, conjunctive use of organic and chemical sources of nutrients, could ameliorate soil health and sustain crop yields. Aim: To assess the potential of the INM approach to enhance the SOC status, soil quality, crop production, and drought adaptation of pearl millet under rainfed conditions. Methods: Nutrient inputs were supplied through mineral fertilizers, organic manures, and a combination of both. SOC sequestration, sustainable yield index, plant‐available N, P, K, and water, bulk density, and KMnO4 ‐oxidizable C were estimated. Results: Higher SOC sequestration rate (0.50 and 0.48 Mg ha −1 y −1 in 50% N (fertilizer) + 50% N (farmyard manure), and 50% N (fertilizer) + 50% N (crop residue), respectively) and significant increase in soil fertility were recorded in organically amended treatments. Improvement of 1 Mg ha −1 of SOC stock in the root zone (0.4 m depth) reduced the severity of drought and increased the yield by 38 kg ha −1 . Plots under organic amendments suffered less yield losses under short‐duration droughts, but this positive effect could only be exploited when the rainfall deficit was up to 25%. Conclusion: Managements that add up to 1.2 Mg ha −1 y −1 SOC are adaptive and climate‐resilient strategies in dry semiarid degraded Inceptisols of the Indo‐Gangetic Plains.